2013
DOI: 10.2215/cjn.06460612
|View full text |Cite
|
Sign up to set email alerts
|

TGF Expression and Macrophage Accumulation in Atherosclerotic Renal Artery Stenosis

Abstract: SummaryBackground and objectives Atherosclerotic renal artery stenosis (ARAS) reduces renal blood flow and is a potential cause of chronic kidney injury, yet little is known regarding inflammatory pathways in this disorder in human participants. This study aimed to examine the hypothesis that reduced renal blood flow (RBF) in ARAS would be associated with tissue TGF-b activation and inflammatory cell accumulation.Design, setting, participants, & measurements This cross-sectional study of ARAS of varying severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 39 publications
5
45
0
Order By: Relevance
“…Under these circumstances cortical hypoxia is overt, leading to activation of the reninangiotensin-aldosterone system, loss of kidney function, rarefaction of small renal vessels, kidney fibrosis, atrophy, and end stage kidney disease designated "ischemic nephropathy". 221,223,[224][225][226][227][228] The connection between atherosclerosis-driven renal hypoxia and CKD is underscored by the finding that the preservation of microvascular architecture by intra-renal administration of vascular endothelial growth factor decreases renal fibrosis and maintains renal hemodynamics and function in an experimental model of renal artery stenosis. 224 In addition, when femoropopliteal angioplasty restores the lumen diameter in patients with generalized atherosclerosis, the incidence of renal disease is dramatically reduced.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Under these circumstances cortical hypoxia is overt, leading to activation of the reninangiotensin-aldosterone system, loss of kidney function, rarefaction of small renal vessels, kidney fibrosis, atrophy, and end stage kidney disease designated "ischemic nephropathy". 221,223,[224][225][226][227][228] The connection between atherosclerosis-driven renal hypoxia and CKD is underscored by the finding that the preservation of microvascular architecture by intra-renal administration of vascular endothelial growth factor decreases renal fibrosis and maintains renal hemodynamics and function in an experimental model of renal artery stenosis. 224 In addition, when femoropopliteal angioplasty restores the lumen diameter in patients with generalized atherosclerosis, the incidence of renal disease is dramatically reduced.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Some have suggested that an index of kidney volume as determined by magnetic resonance with relatively reduced function by radionuclide scan may identify hibernating renal tissue (17). We have been impressed that advancing vascular occlusion does, indeed, produce cortical hypoxia at some point, which was illustrated using BOLD magnetic resonance in the right kidney ( Figure 4); it activated inflammatory injury pathways with accumulation of macrophages, which is known to attract T lymphocytes within the renal parenchyma (18,19). In the past, Kaylor et al (20) advocated for kidney biopsy before surgical renal artery bypass to identify kidney fibrosis and/or atheroembolic disease, although it has not been widely practiced.…”
Section: Discussionmentioning
confidence: 98%
“…40,41 Biopsies from human subjects confirm that cellular infiltrates accumulate in poststenotic kidneys and that inflammatory signaling is correlated with the degree of tissue hypoxia within the poststenotic kidney cortex. 32 34 No such differences regarding B-lymphocyte (CD20 + ) cell counts were observed. Importantly, genetic knockout of downstream pathways (SMAD-3) for TGF-b in models of experimental renovascular disease protects the poststenotic kidney from occlusive vascular injury.…”
Section: Tissue Damage Within the Poststenotic Kidneymentioning
confidence: 94%
“…Histologic inflammation in patients with advanced ARVD is characterized by extensive T cell and macrophage infiltration in addition to fibrosis. 33,34 Hence, it is equally clear that beyond the limits of tolerable reduction in blood flow, overt cortical hypoxia associated with more severe inflammatory injury eventually develops in the poststenotic kidney, as illustrated in Figure 2.…”
Section: Tissue Damage Within the Poststenotic Kidneymentioning
confidence: 99%